Genetic variation in IRF4 expression modulates growth characteristics, tyrosinase expression and interferon‐gamma response in melanocytic cells. (23rd October 2017) - Chhabra, Yash; Yong, Hilary X.L.; Fane, Mitchell E.; Soogrim, Arish; Lim, Wen; Mahiuddin, Dayana Nur; Kim, Reuben S.Q.; Ashcroft, Melinda; Beatson, Scott A.; Ainger, Stephen A.; Smit, Darren J.; Jagirdar, Kasturee; et al.
Summary: A SNP within intron4 of the interferon regulatory factor4 ( IRF4 ) gene, rs12203592*C/T, has been independently associated with pigmentation and age‐specific effects on naevus count in European‐derived populations. We have characterized the cis‐regulatory activity of this intronic region and using human foreskin‐derived melanoblast strains, we have explored the correlation between IRF4 rs12203592 homozygous C/C and T/T genotypes with TYR enzyme activity, supporting its association with pigmentation traits. Further, higher IRF4 protein levels directed by the rs12203592*C allele were associated with increased basal proliferation but decreased cell viability following UVR, an etiological factor in melanoma development. Since UVR, and accompanying IFNγ‐mediated inflammatory response, is associated with melanomagenesis, we evaluated its effects in the context of IRF4 status. Manipulation of IRF4 levels followed by IFNγ treatment revealed a subset of chemokines and immuno‐evasive molecules that are sensitive to IRF4 expression level and genotype including CTLA4 and PD‐L1 .